Degradation of CdTe SC during operation: modeling and experiment - Bolbas, Olexander; Deyneko, Natalya; Yeremenko, Sergey; Kyryllova, Olena; Myrgorod, Oksana; Soshinsky, Olexander; Teliura, Nataliya; Tsapko, Nataliia; Shevchenko, Roman; Yurchyk, Yuliia (Eastern-European Journal of Enterprise Technologies, 2019)
The mechanisms of CdTe SС degradation during operation are experimentally studied. Two mechanisms of degradation of such solar cells are identified. The first is the generation of defects in the transition region, which is caused by excess charge carriers and defects. The second is the increase in the back barrier. The study of the current-voltage and voltage-capacitance characteristics of solar cells allowed proposing a model of degradation of solar cells based on CdTe. It is found that the presence of copper in the back contact is associated with better initial efficiency, but also the fastest degradation during operation. In accordance with the proposed model, the occurrence of additional elementary defects as a result of dissociation of three types of point defect complexes (Cui+–2CuCd–)–, (VCd2––Cui+)–, (2CuCd––VTe+)– is explained. Shunting of the n-p heterojunction and phase transformations from the p+-Cu2-xTe side due to electrodiffusion of CuCd– with p-CdTe at the n-CdS/p-CdTe and p-CdTe/p+-Cu2-xTe boundaries is considered. On the other hand, the diffusion of Cui+ (interstitial copper) into the absorber volume is possible. Electrodiffusion of defects from heterojunctions to the absorber volume is possible, which leads to the compensation of effective acceptor centers and a decrease in the lifetime of minority charge carriers and, accordingly, a decrease in Jph. In addition, there is a growth of shunting metal chains along the longitudinal grain boundaries of p-CdTe between n-p and р-р+ heterojunctions and the possibility of appearance of high-resistance phases of the Cu-Te system. The proposed model explains the possibility of occurrence of the р+ –Cu2–δS phase on the CdS/CdTe boundary, which constrains the passage of the photoactive part of the solar spectrum in p-CdTe